Implementation And Management Of Captive Portal-Based Wireless Network At Smk Negeri 06 Kaur - Rohanita Rohanita; Toibah Umi Kalsum; Hendri Alamsyah (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The computer network at SMK Negeri 06 Kaur is currently connected to the internet. However, the utilization of LAN network, especially the internet, at SMK Negeri 06 Kaur is not yet optimal, as there are still frequent network disruptions such as slow connections and a large amount of inappropriate content being accessed. This study aims to implement wireless network management based on a captive portal at SMK Negeri 06 Kaur. The study employs the Network Development Lite Cycle (NDLC) method. The implementation of captive portal-based network management is expected to improve network performance, enabling users at SMK Negeri 06 Kaur to access the network using a single username on a single device, with bandwidth allocation based on account profiles, and bandwidth management conducted via profiles connected to a simple queue. After implementing captive portal-based network management at SMK Negeri 06 Kaur, the network operates stably and effectively, with results including network speed limits and usage time limits.